Respecting the Red White Flag and National Commitment in the Perspective of Hadith - Rahman, Rahman; Alwi, Zulfahmi; S. Puyu, Darsul; Sawaluddin, Sawaluddin; Triantoro, Dony Arung (ADDIN, 2022)
The purpose of this study is to analyze the phenomena that occur in the community related to respect for the Red and White Flag and national commitment in the perspective of hadith. This study uses a qualitative approach. Qualitative approach is the process of solving the problem under study by describing the object of research in detail. The data collection technique in this study uses library research in the form of documentation studies, namely books that are relevant to hadith texts. The analysis technique used is through three paths, namely: first, data reduction, which is defined as the process of selecting data; secondly, presenting data; thirdly, drawing conclusions. As for the results of this study, the opinion which says that respecting the flag as a shirk behavior does not have a strong argument. They consider that respecting the flag is not included in worship. so respecting the flag means respecting inanimate objects, respecting inanimate objects is including shirk. The implications of the results of this study can at least provide input to policy makers that normatively, mainly based on hadith, that respecting the flag as a symbol of the state is permissible. In general, this research has provided an understanding that respecting the red and white flag is a form of national commitment that must be preserved continuously.